2015
DOI: 10.1371/journal.pone.0145108
|View full text |Cite
|
Sign up to set email alerts
|

High-Copy Overexpression Screening Reveals PDR5 as the Main Doxorubicin Resistance Gene in Yeast

Abstract: Doxorubicin is one of the most potent anticancer drugs used in the treatment of various cancer types. The efficacy of doxorubicin is influenced by the drug resistance mechanisms and its cytotoxicity. In this study, we performed a high-copy screening analysis to find genes that play a role in doxorubicin resistance and found several genes (CUE5, AKL1, CAN1, YHR177W and PDR5) that provide resistance. Among these genes, overexpression of PDR5 provided a remarkable resistance, and deletion of it significantly rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Consistent with this conclusion, Sla1- and End3-defective mutants also exhibited elevated resistance to doxorubicin ( 43 ). Conversely, and also consistent with a role for Akl1 in preventing doxorubicin entry by blocking endocytosis, akl1 Δ cells are hypersensitive to this antibiotic ( 43 , 62 , 63 ).…”
Section: Resultssupporting
confidence: 59%
“…Consistent with this conclusion, Sla1- and End3-defective mutants also exhibited elevated resistance to doxorubicin ( 43 ). Conversely, and also consistent with a role for Akl1 in preventing doxorubicin entry by blocking endocytosis, akl1 Δ cells are hypersensitive to this antibiotic ( 43 , 62 , 63 ).…”
Section: Resultssupporting
confidence: 59%
“…Meiosis and sporulation were observed to be significantly induced in response of yeast cells exposed to doxorubicin. Meiosis was shown to be up-regulated in the presence of doxorubicin in yeast cells 49 . A deficiency in glucose and nitrogen are known to induce meiosis followed G1 arrest of the mitotic cell cycle in diploid yeast cells 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed investigation of the transcriptional response indicated that the genes involved in cellular response to DNA damage and DNA repair were also induced. Several genes functioning in DNA repair were observed to be up-regulated upon doxorubicin exposure 49 . Modular analysis of DEGN also indicated that a module is significantly associated with nucleosome assembly/disassembly and several genes within this module was also found to be involved in DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Observations from other studies illustrate the higher resistance of S. cerevisiae against doxorubicin and the protective effect of glutathione and or metallothioneins [ 70 ]. The assessment of the results should be considered the phase of the cell cycle, which has a direct effect on the toxicity of doxorubicin [ 71 , 72 , 73 , 74 ]. Further investigations are necessary as well as a selective effect on healthy and prostate tumor tissue.…”
Section: Discussionmentioning
confidence: 99%